The impact of material selection and design on the environment in the process of making press tools for garment hanging products in sustainable manufacturing - Amrullah, Radhi Nurvian; Hadi, Syamsul; Rizza, Muhammad Akhlis; Yudiyanto, Eko; Sharif, Safian; Suhaimi, Mohd Azlan (Politeknik Negeri Lhokseumawe, 2024)
The design and material selection used during the manufacturing process significantly impact the environment due to their energy consumption and waste production, including carbon dioxide emissions. This study used the LCA tool eco-indicator to evaluate the environmental impact of producing clothes-hanging machines. Two different press tool designs were analyzed, each using other materials for punch and die. The results indicate that the press tool design 2 with SKD11 punch and die is suitable for long-term use but emits the highest CO2 emissions at 102.33 kg CO2. In contrast, the press tool design 1 with S45C punch and die is suitable for short-term use but emits the lowest CO2 emissions at 69.72 kg CO2.